MANAJEMEN DAN KEPEMIMPINAN PESANTREN: Dinamika Kepemimpinan Kiai di Pesantren - Ramli, Muhamad (STAI AL FALAH Banjarbaru, 2017)
The shifting of leadership pattern in pesantren from individual kiai leadership to collective leadership of the foundation brought a considerable change in pesantren. These changes, especially regarding the authority of the kiai and the participation of religious teachers and students. Through this collective leadership, the succession system is not based on genealogy but emphasized on professionalism. But if there is a cadre who has the ability, in addition to the founding kiai is also a potential cadre, will probably convince the foundation to lift him to be the successor of the leadership of the pesantren because he has prestigious requirements. Ideally, the existence of individual kiai leadership shifts toward the collective leadership of the foundation must bring new nuances to the emergence of democracy, but the problem is not that simple. There are still some serious obstacles that are not easily eliminated, especially from the kiai itself. Keywords: Management, Leadership, Pesantren, Kiai